PENGARUH PENGAWETAN VENIR DENGAN SENYAWA BFCA TERHADAP KETEGUHAN REKAT KAYU LAPIS DARI KAYU KARET (Hevea brasiliensis) - Suwandi Kliwon; M I lskandar; Paribotro Sugitno (Jurnal Penelitian Hasil Hutan, 1992)
This paper   describes  the  treatment  of  1.5  mm   x  20  cm x  20 cm rubberwood  veneer  with BFCA compound of   5 %,  10%.   15 %, 20 %  and  control,  and  3  variations of  extender  in urea  formaldehyde   glue  ,    compositionic    10%, 20% and 30%.The  results  reveal   that  the   concentration of  BFCA  influences    the  bonding   strength  of  rubberwood plywood using Indonesian standard. On the  other  hand  the  effect of percentage   of  extender in  tne compostion  of  urea  formal dehyde   glue  is  not  significant on the bonding strength using Indonesian and Japanese standard. But  the interaction. of concentration of BFCA and percentage  of  extender influences  the bonding strength of plywood.